1993
DOI: 10.1111/j.1439-0329.1993.tb00967.x
|View full text |Cite
|
Sign up to set email alerts
|

The ability of Gremmeniella abietina to hydrolyze polygalacturonic acid

Abstract: Gremmeniella ahietina grew well in media with pectin as the sole carbon source. The fungus secreted at least one enzyme with polygalacturonase activity, and this was induced by addition of pectin to the culture medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…No specific studies, however, are available on enzymes of spores or mycelium of C. pirolata, or in fact in related species to allow us to confirm these findings. Some pathogenic ascomycetes have been reported to excrete enzymes capable of hydrolyzing xylan (Petäistö et al 1992) and pectin, and further can induce polygalacturonase activity in vitro (Petäistö and Kajander 1993). Pectinase activities during pathogenesis are controlled through the physiological conditions of the host cells rather than those of fungi cells (Martin 1980).…”
Section: Discussionmentioning
confidence: 99%
“…No specific studies, however, are available on enzymes of spores or mycelium of C. pirolata, or in fact in related species to allow us to confirm these findings. Some pathogenic ascomycetes have been reported to excrete enzymes capable of hydrolyzing xylan (Petäistö et al 1992) and pectin, and further can induce polygalacturonase activity in vitro (Petäistö and Kajander 1993). Pectinase activities during pathogenesis are controlled through the physiological conditions of the host cells rather than those of fungi cells (Martin 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Polygalacturonase activity was analysed from the culture fluids as described by PETAISTO and KAJANDER (1993), usmg polygalacturonic acid as substrate and galacturonic acid as the standard at a concentration of 5 /imol/ml-25 ^mol/ml. The galacturonic acid produced was measured using the dinitrosalicylic-acid (DNS) method (MiLLER 1959;BAILEY and PESSA 1990).…”
Section: Methodsmentioning
confidence: 99%
“…Gremmeniella abientina has been found to hydrolyse polygalacturonic acid in vitro and the activity is inducible by pectin (PETAISTO and KAJANDER 1993). To characterize the European and North American race of G. abietina, the polygalacturonic-acid hydrolysing activity produced in vitro (nmol galacturonic acid/mg mycelial dry weight) was compared between the European and North American race.…”
Section: Introductionmentioning
confidence: 99%
“…Herron et al 2000). Previous reports (Petäistö and Kajander 1993;Petäistö and Lappi 1996) have proposed that both races (EU and NA) of GAA could potentially secrete at least one enzyme with polygalacturonase activity because G. abietina can grow on a medium with pectin as a sole carbon source. Pectin degradation in the susceptible P. resinosa was also clearly reported using two monoclonal antibodies, JIM-5 and JIM-7, specific to pectin with varying degrees of esterification (Ylimartimo et al 1997).…”
Section: Anti-b-13-glucansmentioning
confidence: 98%
“…This pathogen penetrates its hosts through stomata (Ylimartimo et al 1997) but soon has to deal with various cell walls in order to colonize the host further. In vitro studies revealed that G. abietina is surrounded by an extracellular sheath (ES) containing chitin, galactose, proteins, lipids and polygalacturonic acids (Benhamou and Ouellette 1987a,b) and that it could produce several enzymes such as cellulase, glucanase, xylanase and polygalacturonase (Petäistö et al 1992(Petäistö et al , 1994Petäistö and Kajander 1993;Petäistö and Lappi 1996). Using histo-and cytochemical tests, significant progress has been made in understanding host-pathogen interactions involving G. abietina.…”
Section: Introductionmentioning
confidence: 99%